Identification of physiological traits underlying cultivar differences in drought tolerance in rice and wheat - Praba, M.L.; Cairns, J.E.; Babu, R.C.; Lafitte, H.R. (Wiley, 2009)
Rice is used as a model cereal to study drought response at the molecular level, with the goal of applying results to other cereals. To assess the relevance of results from rice to other species, the kinetics of drought development and plant response of tolerant and susceptible tropical rice (Oryza sativa L.) and subtropical wheat (Triticum aestivum L.) cultivars were compared under vegetative and reproductive stage drought in pot experiments. Water was withheld during reproductive stage until plant available soil moisture content was 30 % of field capacity (FC) or leaf wilting was observed, and then reapplied. Rice reached 30 % FC 9 days after withholding water and wheat after 13 days. Before rewatering, both species reached leaf water potentials of −12 bars and similarly low transpiration rates. Stress reduced leaf relative water content, leaf elongation and membrane stability. When water stress was imposed during reproductive stage, pollen fertility was most affected in wheat, while panicle exsertion and anther dehiscence were severely affected in rice. When water stress was imposed during vegetative stage, wheat was less affected to vegetative stage drought than rice. The nature of differences between tolerant and susceptible cultivars was similar for the two species. However, the differential growth habitats and growth rate of plants needs to be considered in these kinds of experiments.